Aerosol characteristics and types in the marine environments surrounding the East Mediterranean - Middle East (EMME) region during the AQABA campaign. (1st April 2023) - Kaskaoutis, D.G.; Pikridas, M.; Barmpounis, K.; Kassell, G.; Logan, D.; Rigler, M.; Ivančič, M.; Mohammadpour, K.; Mihalopoulos, N.; Lelieveld, J.; Sciare, J.
Abstract: This study analyzes the aerosol optical properties (scattering, absorption coefficients, single scattering albedo), supported by chemical composition measurements, in the marine boundary layer of the East Mediterranean – Middle East (EMME) region, aiming to explore the spatio-temporal variability, aerosol mixing state, sources and dominant types. The measurements were taken during the AQABA (Air Quality and climate change in the Arabian Basin) cruise campaign (1st July – September 1, 2017) from the south of France to Kuwait and back. Both scattering and absorption coefficients for PM1 and PM10 particles maximized in the southern Red Sea, due to continental outflow from East Africa, and in the Arabian/Persian Gulf due to enhanced anthropogenic/industrial emissions, leading to 3-fold sulfate concentrations compared to the other regions. The East Mediterranean exhibited moderate aerosol loading, with high scattering Ångström Exponent (SAE) values (1.98, 1.30 for PM1 and PM10, respectively), which increased in the Suez Canal and the Arabian Gulf due to impact from combustion sources. The aerosol over the Gulf of Aden and the West Arabian Sea was dominated by coarse particles (SAE<1), with higher Ca 2+ concentrations (dust influence). The absorption Ångström Exponent (AAE) remained close to 1, indicative of black carbon (BC) from fossil fuel combustion, while it increased in regions dominated by dust (Gulf of Aden, Arabian Sea). Contrasting aerosol types were identified between the sub-regions using the SAE vs. AAE classification scheme. The " BC-dominated " type prevailed over the East Mediterranean and Suez Canal, while dust mixtures dominated in the Gulf of Aden and the Arabian Sea. Over the Arabian Gulf, mixing of anthropogenic pollution with marine aerosols formed a type with fine particles and low spectral dependence of absorption (AAE<1). Spectral SSA significantly varied along the ship cruise, while it was used for determination of dust influence in the marine environment. Graphical abstract: Image 1 Highlights: Investigation of aerosol optical, chemical properties in the marine environments around the EMME region. Aerosol scattering/absorption maximized in the Persian Gulf due to anthropogenic/industrial aerosol. Contrasting aerosol-type dominance between the marine subregions. Spectral SSA enables to detect the dust imprint in the marine boundary layer. Significant influence of the particle size on aerosol properties and dominant types.